Coplanar capacitive sensors and their applications in non-destructive evaluation: a review - M. Mwelango; Zhu, T.; Wen, K.; Zhang, Z.; Yuan, X.; Li, W.; Yin, X. (Nondestructive testing and evaluation, 2023)
Compared with conventional non-destructive evaluation (NDE) techniques, such as radiography, ultrasound, magnetic particle inspection and eddy current, the coplanar capacitive sensing technique is a newly emerging technique with promising future prospects. Aiming to show the capabilities of coplanar capacitive sensors (CCSs) for NDE, this review paper exploits existing literature on the subject to provide a general systematic overview of the capacitive NDE technique using CCSs. This review focuses on the fundamentals of the technique, factors affecting sensor performance, existing designs of CCSs used for defect detection and finally, the different applications of CCSs for defect detection in different fields of NDE. The existing challenges and future prospects of the CCS technique are also discussed. Amidst the prevalent challenges, obtaining better performance from CCSs has been mostly done by using different geometric designs, but less emphasis has been put on optimising circuit design and choice of sensor component materials. The key to optimisation of sensor performance is rooted in establishing a balance among trade-offs. The various advantages of the technique, compared to conventional NDE techniques, allow for different applications and attest to the potential of the technique for new applications in the future.